2011
DOI: 10.1152/jn.00493.2010
|View full text |Cite
|
Sign up to set email alerts
|

GAD67-GFP+ Neurons in the Nucleus of Roller: A Possible Source of Inhibitory Input to Hypoglossal Motoneurons. I. Morphology and Firing Properties

Abstract: van Brederode JFM, Yanagawa Y, Berger AJ. GAD67-GFPϩ neurons in the Nucleus of Roller: a possible source of inhibitory input to hypoglossal motoneurons. I. Morphology and firing properties. J Neurophysiol 105: 235-248, 2011. First published November 3, 2010 doi:10.1152/jn.00493.2010. In this study we examined the electrophysiological and morphological properties of inhibitory neurons located just ventrolateral to the hypoglossal motor (XII) nucleus in the Nucleus of Roller (NR). In vitro experiments were perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 54 publications
0
22
0
Order By: Relevance
“…As a further negative control, we also confirmed the absence of glycine or GABA immunolabeling in motoneurons exhibiting ChAT immunolabeling in the regions of nucleus ambiguus (NA) and XII nucleus. As a positive control, immunoreactivity of neurons located in the spinal trigeminal nucleus known to contain glycinergic and GABAergic neurons (Kuwana et al, 2006; Winter et al, 2009) or immunoreactivity of neurons located in the nucleus of Roller known to be GABAergic (van Brederode et al, 2011) was corroborated (data not shown) in every experiment. Overall, these immunolabeling results are consistent with our findings from scmRT-PCR experiments showing that pre-BötC intrinsic bursters with contralateral axonal projections are generally not inhibitory neurons, and that intrinsic nonbursters with such axonal projections consisted of a heterogeneous population of neurons with a small percentage (19%) of inhibitory neurons.…”
Section: Resultsmentioning
confidence: 85%
“…As a further negative control, we also confirmed the absence of glycine or GABA immunolabeling in motoneurons exhibiting ChAT immunolabeling in the regions of nucleus ambiguus (NA) and XII nucleus. As a positive control, immunoreactivity of neurons located in the spinal trigeminal nucleus known to contain glycinergic and GABAergic neurons (Kuwana et al, 2006; Winter et al, 2009) or immunoreactivity of neurons located in the nucleus of Roller known to be GABAergic (van Brederode et al, 2011) was corroborated (data not shown) in every experiment. Overall, these immunolabeling results are consistent with our findings from scmRT-PCR experiments showing that pre-BötC intrinsic bursters with contralateral axonal projections are generally not inhibitory neurons, and that intrinsic nonbursters with such axonal projections consisted of a heterogeneous population of neurons with a small percentage (19%) of inhibitory neurons.…”
Section: Resultsmentioning
confidence: 85%
“…Although the origins of GABAergic and glutamatergic synaptic inputs were not identified in this study, previous work by others has provided some potential sources of origin for these inputs (Ugolini, 1995). Neurons in the Nucleus of Roller may be the source of GABAergic neurotransmission to hypoglossal motor neurons, but this has not yet been tested directly (van Brederode et al , 2011). There is a glutamatergic input to hypoglossal neurons from the raphe pallidus which is primarily mediated by both NMDA and non-NMDA glutamate receptors (Bouryi and Lewis, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Cl À -dependent inhibition is critical in burst pattern formation, but is not necessary for rhythm generation itself (Ballanyi et al, 1999;Feldman and Smith, 1989). Here, GABAergic neurons may innervate to the motor neurons in 12 N from pre-BötC and/or premotorneurons (Koizumi et al, 2008(Koizumi et al, , 2013 because of an absence of GAD67-GFP positive cells within the 12 N (van Brederode et al, 2011). It might depend on the specific character of 12 N which does not include GABAergic interneurons.…”
Section: Discussionmentioning
confidence: 99%